2012
DOI: 10.1152/ajpgi.00190.2011
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of gut microbiome with cognition in hepatic encephalopathy

Abstract: Hepatic encephalopathy (HE) has been related to gut bacteria and inflammation in the setting of intestinal barrier dysfunction. We aimed to link the gut microbiome with cognition and inflammation in HE using a systems biology approach. Multitag pyrosequencing (MTPS) was performed on stool of cirrhotics and age-matched controls. Cirrhotics with/without HE underwent cognitive testing, inflammatory cytokines, and endotoxin analysis. Patients with HE were compared with those without HE using a correlation-network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
430
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 478 publications
(458 citation statements)
references
References 46 publications
20
430
4
4
Order By: Relevance
“…15 In the previous report, Bajaj et al have convincingly demonstrated that lactulose withdrawal does not exert a very significant effect on the composition of the fecal microbiome except for a reduction in Faecalibacterium sp. 14 These observations suggest that gut bacterial function, rather than a change in the microbiome composition, may be responsible for the effects of lactulose. 15 Authors hypothesized that cirrhotic patients with HE controlled on daily lactulose can be withdrawn from therapy without cognitive deterioration and those who did experience an episode of HE recurrence have different metabiome interactions than those who remained recurrence-free.…”
Section: The Influence Of Lactulose Withdrawal On the Gut Microbiotamentioning
confidence: 99%
“…15 In the previous report, Bajaj et al have convincingly demonstrated that lactulose withdrawal does not exert a very significant effect on the composition of the fecal microbiome except for a reduction in Faecalibacterium sp. 14 These observations suggest that gut bacterial function, rather than a change in the microbiome composition, may be responsible for the effects of lactulose. 15 Authors hypothesized that cirrhotic patients with HE controlled on daily lactulose can be withdrawn from therapy without cognitive deterioration and those who did experience an episode of HE recurrence have different metabiome interactions than those who remained recurrence-free.…”
Section: The Influence Of Lactulose Withdrawal On the Gut Microbiotamentioning
confidence: 99%
“…A similarly organized 2011 study did not use CDR, however, it did correlate decreased microflora diversity in patients with cirrhosis compared to controls. Diversity was even less in decompensated cirrhotic patients with hepatic encephalopathy (10). The pathology associated with altered CDR is thought to be secondary to reduced production of fatty acids which function to reduce colonic inflammation and reduce intestinal permeability to endotoxins (11).…”
Section: Microbiome Alterations In Cirrhosismentioning
confidence: 99%
“…22 Changes in microbiota have also been implicated in causation of hepatic encephalopathy, but the reports are conflicting. [23][24][25] However, the weight of evidence suggests some relationship between changes in microbiota and cognition. Changes in gut microbiota may also have a role in the pathogenesis of other complications of cirrhosis (eg, spontaneous bacterial peritonitis, hepatorenal syndrome, and cirrhotic …”
Section: Microbiota and Liver Diseasementioning
confidence: 99%